2017
DOI: 10.15406/mojap.2017.03.00087
|View full text |Cite
|
Sign up to set email alerts
|

Amorphometric study of condyloid process of dry human mandible for sexing from its shape

Abstract: The mandible is having the condyloid process which articulates with the temporal fossa to form the temporomandibular joint, on which all the movements occur during the eating, chewing and even on talking also. It is having the articular facet on its head. This articulating facet is having different shapes and sizes which varies according to sex also. The shapes of condyloid processes are classified into four types i.e. convex, flat, rounded and angular. The size of the articular facet varies mandible to mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…In another study round type of condyle was again found to be the most common [24]. Similarly Maqbool et al [13], Al Saedi et al [1] and Gindha et al [7] revealed highly significant difference in condylar type between right and left sides in females and males.…”
Section: Discussionmentioning
confidence: 79%
“…In another study round type of condyle was again found to be the most common [24]. Similarly Maqbool et al [13], Al Saedi et al [1] and Gindha et al [7] revealed highly significant difference in condylar type between right and left sides in females and males.…”
Section: Discussionmentioning
confidence: 79%